2021
DOI: 10.1177/08862605211042602
|View full text |Cite
|
Sign up to set email alerts
|

Child Marriage and Intimate Partner Violence: An Examination of Individual, Community, and National Factors

Abstract: Despite being a human rights violation, child marriage still takes place across the globe. Prior scholarship has shown early marriage to be associated with an increased risk of intimate partner violence (IPV). Drawing on data from the nationally representative Demographic and Health Surveys—conducted in developing and transitional nations where rates of child marriage tend to be higher—the current study provides a cross-national examination of individual-, community-, and national-level predictors of child mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
1
9
0
1
Order By: Relevance
“…Our results add to the previous evidence on the negative impacts of child marriage on young women globally [ 8 , 15 , 26 , 27 , 28 ]. Worldwide, efforts to address child marriage include interventions to prevent marriage before age 15 or age 18, and to delay the age of marriage.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our results add to the previous evidence on the negative impacts of child marriage on young women globally [ 8 , 15 , 26 , 27 , 28 ]. Worldwide, efforts to address child marriage include interventions to prevent marriage before age 15 or age 18, and to delay the age of marriage.…”
Section: Discussionsupporting
confidence: 85%
“…Upon using this approach, it became evident that the likelihood of a girl experiencing IPV is delayed for each increase in the age at first marriage. This approach diverges from most studies in the literature, which rely on specific cut points to analyze the potential consequences of child marriage (e.g., ages 15 or 18) [ 15 ]. In comparison to the previous multi-country studies, our findings also provide more robust evidence of the significant associations for all types of IPV (physical, sexual, and emotional), which were investigated separately.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Later age at marriage, on the other hand, has been found to be associated with a reduced likelihood of reporting IPV in the Congo (Tlapek, 2015). Additionally, a cross-national study of developing countries found an association between women's early ages at marriage and increased prevalence of IPV (Hayes & Protas, 2022). Other crossnational country-specific analyses have reached similar conclusions (Kidman, 2017).…”
Section: Age At Marriagementioning
confidence: 85%